2017
DOI: 10.1038/s41598-017-01581-y
|View full text |Cite
|
Sign up to set email alerts
|

Coaxial 3D bioprinting of self-assembled multicellular heterogeneous tumor fibers

Abstract: Three-dimensional (3D) bioprinting of living structures with cell-laden biomaterials has been achieved in vitro, however, some cell-cell interactions are limited by the existing hydrogel. To better mimic tumor microenvironment, self-assembled multicellular heterogeneous brain tumor fibers have been fabricated by a custom-made coaxial extrusion 3D bioprinting system, with high viability, proliferative activity and efficient tumor-stromal interactions. Therein, in order to further verify the sufficient interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(82 citation statements)
references
References 40 publications
1
80
0
1
Order By: Relevance
“…3D bioprinting is based on computer aided additive manufacturing technology to precisely control the distribution of biomaterials, cells and growth factors in 3D structure to maintain the bioactivity of cells . Compared with seeding cells on 3D scaffolds, 3D bioprinting can better control the position of biomaterials and cells, and promote cell–cell and cell‐ECM interactions . In this study, based on previously reported methods, gelatin, alginate and fibrinogen were chosen for bioink to construct glioma cell model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3D bioprinting is based on computer aided additive manufacturing technology to precisely control the distribution of biomaterials, cells and growth factors in 3D structure to maintain the bioactivity of cells . Compared with seeding cells on 3D scaffolds, 3D bioprinting can better control the position of biomaterials and cells, and promote cell–cell and cell‐ECM interactions . In this study, based on previously reported methods, gelatin, alginate and fibrinogen were chosen for bioink to construct glioma cell model.…”
Section: Discussionmentioning
confidence: 99%
“…26 Compared with seeding cells on 3D scaffolds, 3D bioprinting can better control the position of biomaterials and cells, and promote cell-cell and cell-ECM interactions. 18,27 In this study, based on previously reported methods, 22 gelatin, alginate and fibrinogen were chosen for bioink to construct glioma cell model. The viability of cell was 89.06 AE 3.58% after bioprinting.…”
Section: Discussionmentioning
confidence: 99%
“…Grolman, Zhang, Smith, Moore, and Kilian () built a high‐throughput heterogeneous tumor model containing immune cells and tumor cells by extrusion‐based bioprinting (Figure a). Dai et al () extruded a coaxial 3D model containing glioma stem cells and human MSCs (Figure b). During the culturing period, glioma stem cells fused with MSCs and induced higher gene expression compared with 2D culture models.…”
Section: Techniques For Constructing Heterogeneous Tumor Modelsmentioning
confidence: 99%
“…(b) Coaxial 3D bioprinting cell fibers containing RFP‐expressing tumor cells and GFP‐expressing MSCs. From Dai et al (), copyright© Dai et al CC‐BY 4.0. (c) Construction and characterization of a high‐throughput cell‐patterning platform for printing in a 3D in vitro ovarian cancer co‐culture model.…”
Section: Techniques For Constructing Heterogeneous Tumor Modelsmentioning
confidence: 99%
“…To date, the fabrication of thick 3D constructs (see Figure 2. 2 (a) and (b)) [47,49], and vascularized tissues [50][51][52] (see Figure 2.2 (c)) has been achieved using extrusion printing. Gao et al, [50] reported a strategy to fabricate large-scale organs with built-in microchannels, as shown in…”
Section: Extrusion Printingmentioning
confidence: 99%